Tight junction strand formation by claudin‐10 isoforms and claudin‐10a/‐10b chimeras. Issue 1 (20th June 2017) - Milatz, Susanne; Piontek, Jörg; Hempel, Caroline; Meoli, Luca; Grohe, Christoph; Fromm, Anja; Lee, In‐Fah M.; El‐Athman, Rukeia; Günzel, Dorothee
Abstract: Claudins are integral components of tight junctions (TJs) in epithelia and endothelia. When expressed in cell lines devoid of TJs, claudins are able to form TJ‐like strands at contacts between adjacent cells. According to a current model of TJ strand formation, claudin protomers assemble in an antiparallel double row within the plasma membrane of each cell ( cis ‐interaction) while binding to corresponding double rows from the neighboring cells ( trans ‐interaction). Cis ‐interaction was proposed to involve two interfaces of the protomers' first extracellular segment (extracellular loop (ECL)1). In the current study, three naturally occurring claudin‐10 isoforms and two claudin‐10 chimeras were used to investigate strand formation. All constructs were able to interact in cis (Förster/fluorescence resonance energy transfer (FRET)), to integrate into TJs of MDCK‐C7 cells (confocal laser scanning microscopy), and to form TJ‐like strands in HEK293 cells (freeze‐fracture electron microscopy). Strand formation occurred despite the fact that isoform claudin‐10a_i1 lacks both structural ECL1 elements reported to be crucial for cis ‐interaction. Furthermore, results from FRET experiments on claudin‐10 chimeras indicated that identity of the first transmembrane region rather than ECL1 is decisive for claudin‐10 cis ‐interaction. Therefore, in addition to the interaction interfaces suggested in the current model for TJ strand assembly, alternative interfaces must exist.